Analisis Kinerja BSI Ditinjau Dari Kepuasan Dan Peningkatan Pengguna Internal Berbasis Fast Studi Kasus: STMIK Atma Luhur Pangkalpinang - Bambang Adiwinoto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2017)
Information Systems Division (BSI) as provider and IT manager must be able to perform its function. Quality IT products and services can be measured and perceived by internal users. This research contains two kinds of research, that is research that will test the relation between internal satisfaction with eight independent variable of product quality and IT service and relationship between internal customer performance improvement to eight independent variable of product quality and service of SI / TI. The eight independent variables of product quality and IT services are availability, user friendliness, productivity, durability, timeless of support responsiveness, reliability and integration. The model used in this research is FAST (Framework for the Application of System Thingking). The expected result indicates that there is a positive significant influence between internal customer satisfaction with eight variable of product quality and IT service (reject H0 on hypothesis 1) and there is a positive significant influence between product quality and IT service to internal customer performance improvement (reject H0 on Hypothesis 2). Mann-Whitney analysis results received H0 on hypothesis 3, in other words there is no significant difference in performance aspect between internal customers and Information System Division on the performance of Information System Section on all aspects measured